THE ROLE OF PEER-ASSISTED LEARNING IN ENHANCING CLINICAL COMPETENCE AMONG 3RD-YEAR AND FINAL YEAR MBBS STUDENTS: A PROSPECTIVE STUDY. : JPUMHS;2024:14:04,162-165 .http://doi.org/10.46536/jpumhs/2024/14.04.574 - Syed Azhar Hussain Zaid1, Muhammad Abid2, Muhammad Anwar Bangulzai3, Palwasha Abbasi4, Abdul Hayee Phulphoto5, Shuja Anwar Kazi6, Kashif Rasheed Shaikh7, Muhammad Atif Ata8, Umair Ali Soomro9 Mehwish Jaweed10 (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2024)
BACKGROUND: Peer Assisted Learning PAL has acquired noticeable quality as an instructive methodology that encourages understudy cooperation. By participating in peer drove educating, students build up their mastering and foster fundamental clinical abilities. Be that as it may, the effect of PAL on working on clinical skill, especially among third-year and final year MBBS students, stays a region requiring further investigation. OBJECTIVES: This study planned to assess the viability of Peer Assisted Learning PAL in upgrading clinical skill, explicitly focusing on clinical thinking, correspondence, and cooperation among third-year and last year MBBS students at Suleman Roshan Medical College Tando Adam. METHODS: A prospective cohort study was directed with 85 third-year and last year MBBS students. The PAL mediation included peer-drove case conversations and pretending meetings more than one semester. Pre-and post- assessments were utilized to quantify enhancements in clinical skill. Students input was likewise gathered to evaluate their impression of the PAL approach. RESULTS: The Findings showed prominent enhancements in clinical thinking 83.95%, communication skills 74.07%, and collaboration 82.72% following the mediation. Developmental evaluations uncovered huge score increments p < 0.001. Criticism reviews showed that 88% of students felt more certain about performing clinical assignments. CONCLUSION: The study highlights PAL as a powerful apparatus in clinical training, encouraging dynamic commitment and cooperative learning. Integrating PAL into the educational plan can improve clinical abilities and advance an understudy focused learning climate.